A theory of measuring natural selection and genetic monitoring - A. I. Yuriev (Communicative & Integrative Biology)
Two methods have been compared for determining the value of natural selection in the natural populations. The first method, based on the FST-statistics, employs the dependence of genetic diversity of a species on the value of gene flow between subpopulations of the species, derived from the assumption that all the mutations are close to selective neutrality, and subpopulations effect each other equally. Susceptibility to selection is estimated by the degree of deviation from this relationship between genetic diversity and gene flow in certain species. The second method is based on the probability theory and involves comparison between stabilities of the forms, competing in the population, which is computed using the data about fluctuations in their occurrence in several generations. As applied to the problems of genetic monitoring of rare and valuable species, the first method can be employed for express-assessment of susceptibility of a species to rapid intraspecific changes. The second method is suitable for a long-term and in-depth genetic monitoring of the species subjected to extremely intense natural selection of a disruptive or stabilizing form, which were revealed using the first method. There is a lack of long-term observations of intraspecific genetic variation of rare and protected species. The need for funds that finance long-term genetic research is substantiated.